ORGANIZATION DEVELOPMENT PROJECTION: ANALYSIS OF LEADERSHIP STYLE, TEAMWORK, COMPETENCE EMPLOYEE AND RECRUITMENT PROCESS - Nuraeni Nuraeni; Shaqina Nuruly; Siti Hafnidar Harun; Primadi Candra Susanto (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2022)
This article aims to examine and synthesize literature review studies related to the variables being studied, namely organization development projection, leadership style, teamwork, employee competence and recruitment process, as well as look at the results of research on the variables to be studied and whether there is influence between one variable with other variables. This study uses a literature review by looking for references related to related variables sourced from library research methods, online media, google scholar, direct science, zotero and mendeley. This study provides an overview of several articles obtained by describing the influence between variables. The results of this study are: The Organizational Development Study in the summary of this literature article explicitly focuses on supporting variables that can improve Leadership Style, Team Work, Employee Competence and Recruitment Process. Scientific articles that aim to build research hypotheses about the influence of variables to be used in further research.